FAKTOR-FAKTOR YANG MEMPENGARUHI CALVING INTERVAL SAPI PERANAKAN ONGOLE (PO) DI DESA WAWASAN KECAMATAN TANJUNGSARI KABUPATEN LAMPUNG SELATAN - Harry Setiawan; Sri Suharyati; Siswanto Siswanto; Madi Hartono (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
The purpose of this research was to know the factors and factors value affecting calving interval of Ongole Grade (PO) cattle in Wawasan Village, Tanjungsari District, South Lampung Regency. The Research was conducted on 20 December 2019 – 15 January 2020 using 100 PO cattle in Wawasan Village, Tanjungsari District, South Lampung Regency. This research used census method. Data was analyzed by linear regression using SPSS program. The result showed that calving interval of PO cattle in Wawasan Village, Tanjungsari District, South Lampung Regency was 23.17 ± 6.05 month. The factors that affect the calving interval were, at the farmer level, the breeding experience was negatively associated with a factor of 0.384. At the livestock level, postpartum mating was positively associated with a factor of 0.755 and weaning age was positively associated with a factor of 0.650. At the inseminator level, thawing time is positively associated with a factor of 0.813. Keywords: Calving interval, Factor and factor value, Ongole Grade (PO) cattle